Colophons in fourteenth-century Nepalese manuscripts: materials for the study of the Nepalese Renaissance (I) - Formigatti, C (De Gruyter, 2022)
The present study examines colophons in fourteenth-century Nepalese manuscripts. More precisely, it focuses on manuscripts written between 1320 and 1395 CE as part of an ongoing research about the cultural history of Nepal in this pivotal century, particularly its second half. The first part of the article is devoted to a discussion of the Sanskrit terminology for colophon and an explanation of how to distinguish colophons from other paratextual material in manuscripts. The second part provides general remarks on the syntax of Nepalese colophons including a detailed analysis of sixteen elements occurring in the colophons. The third part consists of diplomatic editions of colophons from the corpus considered for this study. The article concludes with short preliminary conclusions based on the material examined.